Phytochrome A and Phytochrome B Have Overlapping but Distinct Functions in Arabidopsis Development. - Reed, J. W. (1994)
Plant responses to red and far-red light are mediated by a family of photoreceptors called phytochromes. In Arabidopsis thaliana, there are genes encoding at least five phytochromes, and it is of interest to learn if the different phytochromes have overlapping or distinct functions. To address this question for two of the phytochromes in Arabidopsis, we have compared light responses of the wild type with those of a phyA null mutant, a phyB null mutant, and a phyA phyB double mutant. We have found that both phyA and phyB mutants have a deficiency in germination, the phyA mutant in far-red light and the phyB mutant in the dark. Furthermore, the germination defect caused by the phyA mutation in far- red light could be suppressed by a phyB mutation, suggesting that phytochrome B (PHYB) can have an inhibitory as well as a stimulatory effect on germination. In red light, the phyA phyB double mutant, but neither single mutant, had poorly developed cotyledons, as well as reduced red-light induction of CAB gene expression and potentiation of chlorophyll induction. The phyA mutant was deficient in sensing a flowering response inductive photoperiod, suggesting that PHYA participates in sensing daylength. In contrast, the phyB mutant flowered earlier than the wild type (and the phyA mutant) under all photoperiods tested, but responded to an inductive photoperiod. Thus, PHYA and PHYB appear to have complementary functions in controlling germination, seedling development, and flowering. We discuss the implications of these results for possible mechanisms of PHYA and PHYB signal transduction.